Toll-like receptors are critical for clearance of Brucella and play different roles in development of adaptive immunity following aerosol challenge in mice - Pei, Jianwu; Ding, Xicheng; Fan, Yaping; Ficht, Allison R.; Ficht, Thomas A. (Frontiers in Cellular and Infection Microbiology, 2012)
Brucella spp. cause undulant fever in humans and brucellosis in variety of other animals. Both innate and adaptive immunity have been shown to be important in controlling Brucella infection. Toll-like receptors (TLRs) represent a group of pattern recognition receptors (PRRs) that play critical roles in the host innate immune response, as well as development of adaptive immunity. In the current report, we investigated the role of TLR signaling in the clearance of Brucella and development of adaptive immunity in TLR2−/−, TLR4−/−, or MyD88−/− mice following aerosol exposure to B. melitensis 16 M. Consistent with previous reports, MyD88 is required for efficient clearance of Brucella from all three organs (lung, spleen, and liver). The results reveal Th2-skewed immune responses in TLR2−/− mice late in infection and support a TLR2 requirement for efficient clearance of Brucella from the lungs, but not from the spleen or liver. Similarly, TLR4 is required for efficient clearance of Brucella from the lung, but exhibits a minor contribution to clearance from the spleen and no demonstrable contribution to clearance from the liver. Lymphocyte proliferation assays suggest that the TLRs are not involved in the development of cell-mediated memory response to Brucella antigen. Antibody detection reveals that TLR2 and 4 are required to generate early antigen-specific IgG, but not during the late stages of infection. TLR2 and 4 are only transiently required for IgM production and not at all for IgA production. In contrast, MyD88 is essential for antigen specific IgG production late in infection, but is not required for IgM generation over the course of infection. Surprisingly, despite the prominent role for MyD88 in clearance from all tissues, MyD88-knockout mice express significantly higher levels of serum IgA. These results confirm the important role of MyD88 in controlling infection in the spleen while providing evidence of a prominent contribution to protection in other tissues. In addition, although TLR4 and TLR2 contribute little to control of spleen infection, a significant contribution to clearance of lung infection is described.